A CROSS-SECTIONAL ANALYSIS OF RISK FACTORS OF CARDIOVASCULAR DISORDERS IN YOUNG ADULTS - Dr Alina Ajmal; Dr Kashif Ali Hashmi; Dr Saba Khalid; Dr Liaqat Ali; Hira Naqvi; Dr Muhammad Shehzad Khattak (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
This study was conducted to analyze the risk factors of cardiovascular disorders in young people aged (18 to 25) years studying at the Medical University of South Punjab. The present study was a descriptive cross-sectional study conducted in the Cardiology Department of Nishtar Medical University and Hospital, Multan from January 2024 to December 2024. A total of 1000 MBBS students aged from 18-25 years studying at the university were included in the study. Participants’ data was collected through a questionnaire divided into four sections; demographics, clinical data, diet habits and physical activity, and knowledge about cardiovascular diseases. The results showed that among 966 students included, a majority (98.9%) were aged 18 -25 years, 60.8% had normal BMI, and 76.3% with bachelor’s education. The mean systolic blood pressure of samples was 113.2±14.42, the mean diastolic blood pressure was 79.38 ±10.26, and male samples were found with significantly higher SBP and DBP in comparison to female samples (p<0.05). Nearly more than half (68.4%) were physically active, fewer samples were found with daily routines of fruits and vegetables, 47.3% were found with processes or fast food on a regular basis, more than 90% were found with consuming beverages, 20.6% were reported family history of CVD, approximate 79% were reported awareness of CVD risk factors. Outcomes on physical activity, use of beverages, and screen time were significantly associated with gender (p<0.05).On the basis of the statistical findings of this survey, we can conclude that SBP, DBP, physical activity, frequency of fast food, and beverages, screen time, and smoke/sheesha addiction were significant predictors of CVD risk factors among the young population.